Analyzing Spelling Errors and Benefiting from Them to Develop A Spelling Exercise Booklet Based on Constructivist Theory - Wahyuni, Wahyuni; Asrori, Imam; Wargadinata, Wildana (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
This study aims to describe the common Imla errors in Arabic writing and the development of Imla textbooks based on constructivist theory. This research used the qualitative method and R&D method in terms of Brog and Gall. The results of this research and development are Spelling errors with a total of 403 errors, consisting of writing errors in hamzah qath'i and washl, alif, and lam, ta' marbuthah, hamzah in the middle and at the end of words, long sounds, connecting hijaiyyah letters, connecting words. developed is a book for teaching Imla' based on constructivism theory, and the learning process focuses on exploration, clarification, and application activities. The validity of Imla's textbook is the result of expert validation. The overall quality of the book is